Advances in the Silviculture, Management and Research of Black Wattle - Khan, M. A. Waheed (Indian Forester, 1962)
Black Wattle was introduced in Madras State, as early as 1843. Due to high quality of tannin which it produces, extensive plantations have been raised during the recent past. The knowledge, so far gained in the silviculture and management of this species, has been summarised. Recent advances with regard to silviculture, management and research of Black Wattle are reviewed, mainly to reorient the current practices for deriving maximum advantage. The salient features of this advancement are: (1) The correct botanical nomenclature of Black Wattle is Acacia mearnsii de Willd. (Syn. Acacia mollissima Willd.). (2) The maximum production of wood and tannin-containing bark varies with the degree of stocking for each site and age class and for the purposes of efficient management practices it is desirable to define this variability, experimentally and thoroughly. (3) Damaging frost effects of Black Wattle seedlings may be avoided by clear weeding around them and maintaining the soil surface undisturbed. A frost shelterwood of about 100 large-crowned dominant trees per acre is e ffective for natural regeneration. The shelterwood trees should be stripped of bark to kill them. (4) Fertilization requirement is mainly for superphosphate (2 cwt./ac.) and secondarily for lime (5 tons/ac.) and potash (I cwt./ac.) according to the soil properties. Role of trace elements appears to be eminent. (5) Tannin contents in bark vary with age and season. Non-tannin contents are influenced by rainfall and thus age effect is obscured. (6) In conducting research on Black Wattle, it is necessary to observe that: (a) Plot is never less than four trees in width. (b) A plot size of about one tenth acre is advisable. (c) Blocks of plots are square or compactly rectangular. (d) Lattice design is most efficient even with relatively few treatments. (e) Young trees are less variable than mature ones. Research results should, therefore, be assessed at 3 years of age. (f) For fertilization experiments only field trials are useful.